Family Support with the Occurrence of TB Treatment Compliance - Ferdi Riansyah; Maulida Maulida; Gadis Halizasia; Dina Andriani Br Karo; Mela Hayani (Indonesian Journal of Global Health Research, 2024)
Tuberculosis has been known for more than a century since the discovery of the germ that causes Tuberculosis by Robert Koch in 1882. WHO in 1993 said that TB is a very important and serious public health problem throughout the world and is a disease that causes a global emergency, because one in three of the world's population is estimated to have been infected with Mycobacterium tuberculosis (also called Acid-Fast Bacillus = AFB) as the germ that causes TB as evidenced by the Mantoux test. Geographically, the most cases of TB are in Southeast Asia (45.6%), Africa (23.3%) and the Western Pacific (17.8%), and the smallest in the Eastern Mediterranean (8.1%), The Americas (2.9%) and Europe (2.2%). This study uses a quantitative approach, by formulating a hypothesis which is then subjected to statistical testing to accept or reject the hypothesis. This study aims to determine the relationship between family support and treatment compliance in tuberculosis patients. Based on the table above about instrumental support shows that less instrumental support (10%) in non-compliant patients is lower compared to good instrumental support (57.1%). Based on statistical tests, the p-value on instrumental support is 0.001 which means there is a significant relationship between instrumental support and tuberculosis treatment compliance.